A Universidade Federal de Santa Maria um espaço de turismo e aprendizado para o público infantil - Almeida, Camila Ramos de (2017)
The present research presents a proposal about the importance of the creation and distribution of materials of diffusion of the Federal University of Santa Maria - UFSM to the infantile public. These materials consider characteristics and specific cognitive abilities for the development of this age group, determined by children from 04 to 07 years of age. UFSM, besides being one of the main educational institutions of the State and Country, is becoming more and more established as the holder of a collection of different types of cultural heritage, aimed at different audiences, from families to students from different regions of the country and from world, who seek and find in their spaces production of knowledge, leisure, culture and fun. In this way, this study sought to think and construct proposals for playful and pedagogical dissemination materials that can be distributed to the children's audience and that present places of interest that can be explored within the University. Thus, the products elaborated in this master's degree can contribute to the formation of affective bonds of the target public with the visited places, helping in their preservation and divulgation and consequently, would also help in the formation of more careful citizens, zealous and preoccupied with the historical and cultural assets of your neighborhood, city and region